Answer:
-102
Step-by-step explanation:
2x3=6
6+7 = 13
13x2=26
26-4=22
2x2=4
4+4=8
8x-10=-80
-80 - 22 = -102
Hope this helps
To subtract the given expressions, first, simplify each expression separately by combining like terms. Then subtract the second expression from the first expression by distributing a negative sign and adding it to the first expression.
To subtract the given expressions, (2x^3+7x^2-4) - (2x^2+4x-10), we need to simplify each expression separately and then subtract them. First, combine like terms within each expression. Then, subtract the terms of the second expression from the first expression. This can be done by distributing a negative sign to each term in the second expression and then adding it to the first expression.
So, (2x^3+7x^2-4) - (2x^2+4x-10) = 2x^3+7x^2-4 - 2x^2-4x+10.
Combining like terms, we get 2x^3+(7x^2-2x^2)+(-4-4x)+(10). Simplifying further, we have 2x^3 + 5x^2 - 4x + 6. Therefore, the result of the subtraction is 2x^3 + 5x^2 - 4x + 6.
#SPJ2
ASAP
$48 is the cost this month. You multiplied 60 and $0.05, and then added $45.
The solution is A = √50
The value of the equation is A = √50 or 50^( 1/2 )
Equations are mathematical statements with two algebraic expressions flanking the equals (=) sign on either side.
It demonstrates the equality of the relationship between the expressions printed on the left and right sides.
Coefficients, variables, operators, constants, terms, expressions, and the equal to sign are some of the components of an equation. The "=" sign and terms on both sides must always be present when writing an equation.
Given data ,
Let the number be represented as A
Now , the equation will be
A² = 50 be equation (1)
On simplifying the equation , we get
Taking square roots on both sides of the equation , we get
A = 50 ^ ( 1/2 )
On further simplification , we get
A = √50
The value of A is A = 7.0710678118654752440084436210485
Therefore , the value of A is √50
Hence , the equation is A = √50
To learn more about equations click :
#SPJ2
Answer:
d = 90 (t) rule for function and travel d = 1250 feet .
Step-by-step explanation:
Given : A cheetah travels at a rate of 90 feet per second.The distance d traveled by the cheetah is a function of seconds traveled t.
To find : Write a rule for the function.How far will the cheetah travel in 25 seconds.
Solution : Cheetah travel in one second = 90 feet.
Function would be : d = 90 (t).
For t = 25 second then ,
d = 90 ( 25 ).
d = 2250 feet .
Therefore, d = 90 (t) rule for function and travel d = 2250 feet .